THE QUALITY OF EMBRYOS RESULTED FROM IN VITRO FERTILIZATION BY USING FROZEN SEMEN THAWED IN DIFFERENT TEMPERATURES - Yasri, Rakhmi; Handarini, Ristika; Imron, Muhammad (Jurnal Peternakan Nusantara, 2017)
In vitro fertilization technology in cows is an effort done to utilize ovary waste from cows slughtered in abbatoir. This study was aimed at assessing the qualiy of embryos resulted from in vitro fertilization by using frozen semen thawed in different temperatures. In order to get qualty semen, standardized thawing method is required. It was expected from this study that an optimum thawing temperature for frozen semen was determined to obtain quality transferable embryos. Three treatments consisting of thawing with water 37°C for 30 second (T1), thawing with water 25°C for 30 second (T2), and thawing with water 10°C for 30 second (T3). Data were subjected to an an anlysis of variance (Anova) and a Duncan test. Results showed that oocytes fertilized with frozen semen thawed at 37°C and 10°C had higher fertilization rate and excellent-grade embryos (P<0.05) than did the ones fertilized with frozen semen thawed at 25°C. However, no different effect of thawing temperatures was found on transferable and degenerated embryos (P>0.05). It was concluded that embryos fertilized with Brahman frozen semen in thawed at 37°C had the highest number of embryos (49.66±2.88) and excellent-grade embryos (22.00±4.35). Key words: Embryo quality, In vitro fertilization, frozen semen thawing, Brahman bull.